Losartan Reduces Insulin Resistance by Inhibiting Oxidative Stress and Enhancing Insulin Signaling Transduction - Pan, Y.; Qiao, Q. Y.; Pan, L. H.; Zhou, D. C.; Hu, C.; Gu, H. F.; Fu, S. K.; Liu, X. L.; Jin, H. M. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Background: Inhibition of the rennin-angiotensin system (RAS) could reduce insulin resistance in patients with hypertension and diabetic kidney disease (DKD), but whether the effect of losartan on insulin resistance is associated with reduction of oxidative stress and enhancement of insulin signaling transduction has not been fully elucidated.Methods: 130 patients with type 2 DKD were randomly assigned into 2 groups, the losartan group (n=65, 100 mg orally daily for 12 months) and the amlodipine group (n=65, 10 mg orally daily for 12 months). Oxidative stress markers in plasma, urine concentrations of 8-hydroxy-2’-deoxyguanosine (8-OHdG) and nitrotyrosine (NT) as well as SOD activity were measured by ELISA. After in vitro treatment with different doses of losartan (10, 100 μmol/L) or amlodipine for 48 h, the size of H2O2-induced adipocytes and glucose consumption were measured. Western blot was performed to investigate IRS-1 serine phosphorylation level as well as the protein expressions of phosphorylated insulin receptor (pIR), phosphatidylinositol 3- kinase (PI3K) and insulin receptor substrate 1 (IRS-1) in 3T3-L1 adipocytes.Results: After 12-month treatment, there were no significant differences in systolic and diastolic blood pressures decreases, plasma fasting blood glucose and HbA1c between the 2 groups. Compared with amlodipine group, fasting blood insulin levels and insulin resistance index (HOMA-IR) were significantly decreased in losartan group, and in addition, the circulating levels of 8-OHdG and NT were significantly decreased in losartan group, while the serum SOD activity was enhanced. There were significant positively correlations of HOMA-IR with inflammatory oxidative stress markers. In vitro study showed that losartan could increase glucose uptake in 3T3-L1 adipocytes (P<0.01) and decrease adipocyte size (P<0.01), while amlodipine can’t. Losartan can also enhance adiponectin (P<0.05) and decrease TNF-α (P<0.05) and IL-6 (P<0.01) secretion, while amlodipine can’t. The protein expressions of pIR, IRS-1 and PI3K were significantly increased after treatment with losartan (P<0.01), while the level of IRS-1 serine phosphorylation was decreased (P<0.01), which could be blocked by specific PI3K inhibitor wortmannin.Conclusions: These results suggest that the effect of losartan on insulin resistance is associated with the reduction of oxidative stress and inflammation in patients with type 2 DKD as well as the activation of insulin signal pathway in insulin-resistance 3T3-L1 adipocytes through modulation of PI3K pathway. (Clinical Trials. gov number, NCT 00774904)
Keywords: losartan; adipocyte; insulin resistance; insulin receptor; oxidative stress